Examining the use of methodological pluralism in Library and Information Science empirical research produced by Pakistani authors - Ullah, Ahsan; Ameen, Kanwal (Malaysian Journal of Library and Information Science, 2022)
Methodological pluralism or plurality is considered as the employment of more than one method in an inquiry. Methodological pluralism can be categorised into mixed methods and multi-method. The current study explored the use of methodological pluralism in Library and Information Science (LIS) research produced by Pakistani authors. Qualitative content analysis was used to explore latent and manifest use of methodologies in research articles authored by Pakistani published between 2001 and 2016 in national and international journals. Multiple searching strategies were used to identify the articles published in international journals. Findings show that high majority of Pakistani authors did not use the terms mixed methods and multi-method in the description of methodology. Nearly one third (30%) research articles used more than one method. The share of multi-method research (16%) is slightly higher than mixed methods research (14%). In multi-methods articles, combining of quantitative methods was less prevalent as compared to qualitative methods. Multi-method quantitative was used in only six articles. In case of multi-method qualitative design, interviews, personal communication and discussion with experts, literature review and content analysis are the most popular methods. In mixed methods research, interview and questionnaire are the most used methods. Growth in methodological pluralism is half than growth of articles with single method. Knowing and elaboration of the differentiation in mixed methods and multi-method can help in the education and use of methodological pluralism among LIS researchers. Authors should use and explore methodological plurality by treating multi-method designs as separate from mixed method designs.